A Review on Nature Based Sunscreen Agents. Issue 1 (1st February 2023) - Sharma, Mehak; Sharma, Ajay
Abstract: In recent decades, there has been a huge increase in the ultraviolet radiations of the sun hitting the surface of the earth that has eventually resulted in the depletion of the ozone layer. Keeping this thing in mind, it is a must to protect our skin from these rays as they cause harmful damage to human skin. These rays cause hyperpigmentation, photoaging, erythema, skin cancer and many other problems. Using sunscreen to protect our skin from them is the most popular way these days. Sunscreens are regularly tested and assigned a specific sun protection factor (SPF) according to their efficacy to protect skin. Most of synthetic sunscreen agents are very harmful for us as they cause Leukocytosis, allergic reactions, damage DNA(deoxyribonucleic acid), reduction of organ weight and evennanemia. Many Compounds that are obtained from nature for example lignin, flavonoids, aloe Vera, tomato, Shea butter, jojoba oil, evening primrose oil, saffron, almond, etc.(Et cetra) are also efficient in protecting our skin from these rays. They also have higher antioxidant capacities and many other paybacks as compared to synthetic ones. In this paper, an effort has been made to review these natural sunscreen agents so as to make people aware about their beneficial properties.